2006
DOI: 10.1088/1126-6708/2006/11/089
|View full text |Cite
|
Sign up to set email alerts
|

Embedding of theories withSU(2|4)symmetry into the plane wave matrix model

Abstract: We study theories with SU (2|4) symmetry, which include the plane wave matrix model, 2 + 1 SYM on R × S 2 and N = 4 SYM on R × S 3 /Z k . All these theories possess many vacua. From Lin-Maldacena's method which gives the gravity dual of each vacuum, it is predicted that the theory around each vacuum of 2 + 1 SYM on R × S 2 and N = 4 SYM on R × S 3 /Z k is embedded in the plane wave matrix model. We show this directly on the gauge theory side. We clearly reveal relationships among the spherical harmonics on S 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
144
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 70 publications
(150 citation statements)
references
References 45 publications
6
144
0
Order By: Relevance
“…In [15], Takayama and three of the present authors found relationships among the SU(2|4) symmetric theories. Here the SU(2|4) symmetric theories include N = 4 super Yang Mills (SYM) on R × S 3 /Z k , 2+1 SYM on R × S 2 [16] and the plane wave matrix model (PWMM) [17].…”
Section: Introduction and Conclusionsupporting
confidence: 56%
See 1 more Smart Citation
“…In [15], Takayama and three of the present authors found relationships among the SU(2|4) symmetric theories. Here the SU(2|4) symmetric theories include N = 4 super Yang Mills (SYM) on R × S 3 /Z k , 2+1 SYM on R × S 2 [16] and the plane wave matrix model (PWMM) [17].…”
Section: Introduction and Conclusionsupporting
confidence: 56%
“…Combining these two equivalences, we can say that the theory around each vacuum of N = 4 SYM on R × S 3 /Z k is realized in PWMM. In [15], these equivalences were shown directly on the gauge theory side. The results in [15] not only serve as a nontrivial check of the gauge/gravity correspondence for the SU(2|4) theories, but they are also interesting in the following aspects.…”
Section: Introduction and Conclusionmentioning
confidence: 93%
“…The thermodynamics of large N gauge theory on R × S 2 should be also interesting. The relation among these models at zero temperature has been discussed in [6,47,48,8], and it is worth while investigating the relation among their thermodynamics.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Along the thermal cycle we assign the anti-periodic boundary condition for the fermions. 8 We start from fixing the gauge symmetry and then introduce the Faddeev-Popov determinant conjugate to the gauge fixing. We adopt the Coulomb gauge…”
Section: Path Integral Formulationmentioning
confidence: 99%
See 1 more Smart Citation